Decomposable rubber composition, rubber member, sealing member, and method for producing degradable rubber composition
By using a decomposition rubber composition containing a high content of acidic hydrolysis promoter in the sealing member, the problem that decomposition rubber components in the prior art are difficult to naturally be reduced, and automatic disintegration and removal are achieved after exposure to fluids such as water. effect.
Patent Information
- Application Number
- CN202380053749.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-18
- Publication Date
- 2025-02-18
AI Technical Summary
After the decomposition rubber component in the conventional sealing member is exposed to a fluid such as water, although the hardness becomes zero, it still maintains its shape and is difficult to naturally slice, resulting in difficulty in removing it.
The decomposition rubber composition containing a decomposition rubber component and an acidic hydrolysis promoter is used to promote hydrolysis of rubber molecules by an acidic hydrolysis promoter in contact with water. It contains 40 parts by mass or more of acidic relative to 100 parts by mass of the decomposition rubber component. Hydrolysis promoter.
After exposure to a fluid such as water, the rubber member can naturally disintegrate and become smaller, avoiding the need for external stress application and simplifying the removal process.
Smart Images

Figure CN119487282A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a degradable rubber composition, a rubber member, a sealing member and a method for producing the degradable rubber composition, and in particular to a degradable rubber composition, a rubber member, a sealing member and a method for producing the degradable rubber composition that naturally disintegrate after a predetermined period of time. Background Art
[0002] In the past, in order to extract hydrocarbon resources such as oil and natural gas in underground layers, the following methods were used: Figure 6 Hydraulic fracturing is shown. Figure 6 This is an explanatory diagram showing an overview of the hydraulic fracturing method. In the hydraulic fracturing method, first, an underground layer 50 is excavated from a pit 10 on the surface 11 by a drill bit or the like, and an excavation hole 13 is formed until a production layer 51 in which hydrocarbon resources are distributed and confined underground at a great depth of, for example, several thousand meters is reached. Next, a fluid such as water is injected into the formed excavation hole 13 at high pressure, thereby breaking the bedrock of the production layer 51 and causing cracks 15 in the bedrock of the production layer 51. The hydrocarbon resources confined in the production layer 51 are released from the cracks 15 thus generated (for example, refer to Patent Document 1).
[0003] In the hydraulic fracturing method, in order to generate cracks 15 in the production layer 51 by utilizing the pressure of the fluid, it is necessary to seal the excavation hole 13 at one or more locations using a sealing member 100 such as a fracturing plug, thereby forming a space sealed by the sealing member 100 in a part of the excavation hole 13. In this case, the sealing member 100 needs to have the function of inhibiting the fluid from flowing out of the space.
[0004] On the other hand, in order to extract hydrocarbon resources released by hydraulic fracturing through the excavation hole 13, it is necessary to remove the sealing member 100 from the excavation hole 13. As a method for making it easy to remove the sealing member 100 from the excavation hole 13, there is a method of using the sealing member 100 in the excavation hole 13, wherein the sealing member 100 is decomposed by being exposed to an environment with a fluid such as water for a predetermined time. As such a sealing member 100, for example, a sealing member composed of a resin member and a rubber member is known, wherein the resin member is formed of a decomposable resin such as polylactic acid, and the rubber member is formed of a decomposable rubber component.
[0005] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2015-59376 Summary of the invention
[0006] Technical problem to be solved by the invention However, the decomposable rubber component used as the rubber component of the above-mentioned sealing component 100 can maintain a gel-like or clay-like state with high viscosity even if it is exposed to an environment with a fluid such as water for more than a specified time and is hydrolyzed. Specifically, even if the hardness of the previous decomposable rubber component becomes 0, it will not be fragmented as long as no force is applied from the outside. That is, in the previous sealing component 100, the rubber component maintains its shape and remains in the excavation hole 13 in an undisintegrated state. In order to remove the remaining sealing component 100 from the excavation hole 13, it is necessary to insert a drill bit or the like into the excavation hole 13, and use the drill bit or the like to crush the sealing component 100, thereby applying stress from the outside of the sealing component 100 to fragment it. Therefore, due to its high viscosity, it is entangled with the front end of the drill bit and hinders the operation, which may cause obstacles to the separation operation of the recovered liquid. Under the above circumstances, there is a demand for a rubber member that has sealing performance as the sealing member 100 and can be easily removed by being cut into small pieces even without external stress after being continuously exposed to a fluid such as water for a predetermined time.
[0007] The present invention has been made in view of the above circumstances, and an exemplified technical problem is to provide a degradable rubber composition, a rubber member, a sealing member, and a method for producing a degradable rubber composition, wherein the degradable rubber composition has a sealing performance as a rubber member as a sealing member and can be easily removed by being broken into small pieces even when no stress is applied from the outside after being continuously exposed to a fluid such as water for a predetermined period of time.
[0008] Technical solutions for solving technical problems In order to solve the above-mentioned technical problems, the present invention has the following configurations.
[0009] (1) A degradable rubber composition comprising a degradable rubber component and an acidic hydrolysis accelerator, wherein the degradable rubber component comprises a kneadable rubber material composed of rubber molecules capable of hydrolysis, and the acidic hydrolysis accelerator is a powder that exhibits acidity upon contact with water and accelerates the hydrolysis of the rubber molecules upon contact with water, wherein the acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0010] (2) A rubber member formed from the degradable rubber composition described in (1) above.
[0011] (3) A sealing member including the rubber member described in (2) above as at least a part thereof.
[0012] (4) A method for producing a degradable rubber composition, comprising a kneading step of kneading raw materials, the raw materials containing a degradable rubber component and an acidic hydrolysis accelerator, the degradable rubber component comprising a kneadable rubber material composed of rubber molecules capable of hydrolyzing, the acidic hydrolysis accelerator being a powder that exhibits acidity upon contact with water and that accelerates the hydrolysis of the rubber molecules upon contact with water, the acidic hydrolysis accelerator being contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0013] Hereinafter, further objects and other features of the present invention will be described through preferred embodiments described with reference to the accompanying drawings.
[0014] Effects of the Invention According to the present invention, there can be provided a degradable rubber composition, a rubber member, a sealing member, and a method for producing a degradable rubber composition, wherein the degradable rubber composition has a sealing property as a rubber member and can be easily removed by being broken into small pieces even when no stress is applied from the outside after being continuously exposed to a fluid such as water for a predetermined period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram showing a sealing member formed using the degradable rubber composition of the first embodiment.
[0016] Figure 2 This is a graph showing the results of measuring the surface hardness of the rubber samples of Example 1 and Comparative Examples 1 and 2.
[0017] Figure 3 Schematic diagram showing the state of the rubber sample of Example 1 before and after natural disintegration.
[0018] Figure 4 It is a schematic diagram showing the state of the rubber samples of Comparative Examples 1 and 2 after decomposition.
[0019] Figure 5 This is a graph showing the results of measuring the surface hardness of the rubber samples of Examples 2 to 4.
[0020] Figure 6 This is an explanatory diagram showing an outline of a conventional hydraulic fracturing method. DETAILED DESCRIPTION
[0021] [Implementation Method 1] Hereinafter, the degradable rubber composition according to the first embodiment (hereinafter, sometimes simply referred to as “degradable rubber composition”) will be described.
[0022] [Degradable rubber composition] The degradable rubber composition contains a degradable rubber component and a hydrolysis accelerator, and is suitable for use as a material for a rubber member constituting a sealing member used in, for example, hydraulic fracturing. The rubber member formed using the degradable rubber composition has the sealing performance of a rubber member as a sealing member.
[0023] In addition, the rubber component formed using the degradable rubber composition has the following characteristics: after being continuously exposed to a fluid such as water for a predetermined time, it is broken into small pieces even if no stress is applied from the outside. Specifically, the degradable rubber component of the present embodiment will break into small pieces (natural disintegration described later) even if no force is applied from the outside at the stage where the hardness becomes 0. In addition, the "predetermined time" refers to the time when the rubber component is initially exposed to a fluid such as water and then continuously exposed, and hydrolysis is carried out until the rubber component naturally disintegrates. In the present embodiment, the time until the rubber component naturally disintegrates refers to the time when the rubber component is initially exposed to a fluid such as water and then continuously exposed, and hydrolysis is carried out until the rubber component naturally disintegrates.
[0024] Here, the "natural disintegration" of the rubber component means that after the rubber component is continuously exposed to a fluid such as water for a specified time, the rubber component cannot maintain its shape and disintegrates into small pieces. If the temperature conditions are different, the "prescribed time" may also change, and the performance of the rubber component needs to be evaluated under certain conditions. In the present embodiment, the time (prescribed time) until the rubber component naturally disintegrates is evaluated under certain conditions of continuous exposure in water at 93°C. In the past, it was known that the time until the surface hardness (HsA) of the rubber component composed of hydrolyzable rubber molecules becomes 0 (zero) under continuous exposure in water at 93°C requires a specified number of days (for example, 7 days). It should be noted that the surface hardness (HsA) of the rubber component becomes 0 (zero) and the natural disintegration of the rubber component is different. That is, even if the surface hardness (HsA) of the rubber component becomes 0 (zero), there is a situation where the shape of the rubber component is maintained, and if stress is not applied from the outside of the rubber component, it will not be fragmented. Below, each component of the decomposable rubber composition is described in turn. It should be noted that the details of the hydraulic fracturing method and the sealing member will be described below.
[0025] [Degradable rubber component] The decomposable rubber component includes a kneading type rubber material. Here, "kneading type rubber material" refers to a kneading type rubber material, i.e., a rubber material that can be kneaded. The kneading type rubber material is a rubber material that is solid at room temperature in the state before vulcanization, and is distinguished from a liquid injection type rubber material. The kneading type rubber material is solid at room temperature, and is therefore suitable for kneading using, for example, a kneading machine, a roller, etc. Even if a large amount of powdered additives are added, the additives can be uniformly dispersed in the kneading type rubber material by kneading. It should be noted that in the case of a liquid injection type rubber material, since it is a liquid at room temperature, if a large amount of powdered additives are added, the solubility limit may be reached, phase separation may occur, or the additives may clump and become difficult to disperse uniformly.
[0026] As the kneading type rubber material, there can be mentioned a material containing at least one selected from polyurethane rubber, natural rubber, isoprene rubber, ethylene propylene rubber, butyl rubber, styrene rubber, acrylic rubber, aliphatic polyester rubber, and chloroprene rubber. It should be noted that in the present embodiment, thermoplastic elastomers such as polyester thermoplastic elastomers and polyamide thermoplastic elastomers, which are materials having properties similar to those of the kneading type rubber material, can also be included in the concept of the kneading type rubber material.
[0027] The kneading type rubber material is composed of rubber molecules that can be hydrolyzed. As the rubber molecules that can be hydrolyzed, it is preferred that the rubber molecules have a functional group that can be hydrolyzed in the main chain of the rubber molecules. The rubber molecules may have a functional group that can be hydrolyzed not only in the main chain but also in the cross-linked part. Examples of the functional group that can be hydrolyzed include carbamate groups, ester groups, amide groups, carboxyl groups, hydroxyl groups, silyl groups, etc. A part of the repeating units constituting the rubber molecules may have a functional group that can be hydrolyzed, or all of them may have a functional group that can be hydrolyzed.
[0028] The mass average molecular weight of the rubber molecules constituting the mixed rubber material is preferably, for example, 10,000 or more. If the mass average molecular weight is 10,000 or more, there is a tendency that the handling operability as the mixed rubber becomes good. It should be noted that the mass average molecular weight of the rubber molecules constituting the mixed rubber material is adjusted according to the content ratio of the hydrolysis accelerator and the hydrolysis inhibitor described later, so that the time from exposure to a fluid such as water to the natural disintegration of the rubber member can be controlled.
[0029] As a kneading type rubber material, polyurethane rubber is preferred from the viewpoint of controlling the sealing performance such as hardness and elasticity as a rubber component and controlling the decomposition performance and disintegration performance. Polyurethane rubber includes ester type polyurethane rubber, ether type polyurethane rubber, etc., and ester type polyurethane rubber with a functional group that can be hydrolyzed is particularly preferred. In addition, polyurethane rubber, in addition to the kneading type, also includes thermoplastic type, liquid injection type, etc., but since the hydrolysis accelerator described later is a powder, in order to make the decomposable rubber composition contain a hydrolysis accelerator of more than a specified amount, kneading type polyurethane rubber is preferred.
[0030] The degradable rubber component preferably contains a kneaded rubber material as a main component. The degradable rubber component may contain a rubber material other than the kneaded rubber material as long as the properties of the kneaded rubber material used in the present embodiment are not affected.
[0031] [Hydrolysis accelerator] The hydrolysis accelerator is a powder that becomes acidic or alkaline when in contact with water and is a component that promotes the hydrolysis of rubber molecules in the degradable rubber component. Here, "powder" refers to a substance that is in powder or granular form at room temperature and not in contact with water (dry state), and the particle size is 200 μ m or less. When the powder comes into contact with water, its aqueous solution becomes acidic or alkaline. The acidic or alkaline aqueous solution promotes the hydrolysis of rubber molecules. In the present embodiment, the powder that shows acidity when in contact with water and promotes the hydrolysis of rubber molecules of the degradable rubber component when in contact with water is referred to as an acidic hydrolysis accelerator. In the present embodiment, the powder that shows alkalinity when in contact with water and promotes the hydrolysis of rubber molecules of the degradable rubber component when in contact with water is referred to as an alkaline hydrolysis accelerator.
[0032] As the acidic hydrolysis accelerator, for example, mineral powders such as silicon dioxide, clay, talc, aluminum sulfate, barium sulfate, calcium sulfate, and alumina colloid can be cited. It should be noted that the acidic hydrolysis accelerator is not limited to mineral powders. As the acidic hydrolysis accelerator, these substances can be used alone, or a plurality of substances can be used in combination.
[0033] In the decomposable rubber composition, the content ratio of the acidic hydrolysis accelerator is 10 parts by mass or more relative to 100 parts by mass of the decomposable rubber component, preferably 20 parts by mass or more, more preferably 40 parts by mass or more, and particularly preferably 40 parts by mass. If the content ratio of the acidic hydrolysis accelerator is 10 parts by mass or more, the decomposition of the decomposable rubber component is promoted, and the decomposed substance (hereinafter referred to as the decomposed product) becomes clay-like and maintains the clay-like shape. If the content ratio of the acidic hydrolysis accelerator is 20 parts by mass or more, the decomposed product disintegrates due to external force. If the content ratio of the acidic hydrolysis accelerator is 40 parts by mass or more, the decomposed product disintegrates naturally without applying external force. By making the content ratio of the acidic hydrolysis accelerator in the decomposable rubber composition 40 parts by mass or more relative to 100 parts by mass of the decomposable rubber component, a decomposable rubber composition constituting a sealing member can be obtained, wherein the sealing member is exposed to a fluid such as water for a specified time to appropriately disintegrate the rubber molecules naturally, and can be easily removed by flakes even if stress is not applied from the outside.
[0034] The hydrolysis accelerator includes an acidic hydrolysis accelerator, and may further include an alkaline hydrolysis accelerator within a range not impairing the effect of the acidic hydrolysis accelerator.
[0035] As the alkaline hydrolysis accelerator, for example, alkaline oxides such as metal oxide particles, salts of weak acids and strong bases, or metal hydroxides can be mentioned. As the alkaline oxide, for example, magnesium oxide, potassium oxide, or calcium oxide can be mentioned. As the salt of weak acids and strong bases, for example, sodium carbonate, sodium bicarbonate, or calcium carbonate can be mentioned. As the metal hydroxide, for example, sodium hydroxide or potassium hydroxide can be mentioned. It should be noted that the alkaline hydrolysis accelerator is not limited to the above-mentioned alkaline oxides, salts of weak acids and strong bases, or metal hydroxides. As the alkaline hydrolysis accelerator, these substances can be used alone, or a variety of substances can be used in combination.
[0036] In the degradable rubber composition, the content of the alkaline hydrolysis accelerator is 1 part by mass or more relative to 100 parts by mass of the degradable rubber component. By setting the content of the alkaline hydrolysis accelerator in the degradable rubber composition to 1 part by mass or more relative to 100 parts by mass of the degradable rubber component, the hydrolysis of the rubber molecules can be further accelerated by continuous exposure to a fluid such as water, thereby shortening the time until the rubber molecules naturally disintegrate.
[0037] [Hydrolysis Inhibitor] The degradable rubber composition may further contain a hydrolysis inhibitor in addition to the degradable rubber component and the hydrolysis accelerator. The hydrolysis inhibitor is a component that inhibits the hydrolysis of rubber molecules promoted by the hydrolysis accelerator. As the hydrolysis inhibitor, for example, a component that reacts with the carboxylic acid at the carboxyl terminal generated by the hydrolysis of the rubber molecules to inhibit the chain reaction of the hydrolysis reaction can be used.
[0038] Examples of the hydrolysis inhibitor include polymer carbodiimide compounds, etc. As the hydrolysis inhibitor, these may be used alone or in combination of a plurality of them.
[0039] The properties of the hydrolysis inhibitor are not particularly limited, and for example, a powdered hydrolysis inhibitor may be used. By using a kneading type rubber material, the powdered hydrolysis inhibitor can be kneaded well.
[0040] In the decomposable rubber composition, the content of the hydrolysis inhibitor is preferably 1 part by mass or more relative to 100 parts by mass of the decomposable rubber component. The content of the hydrolysis inhibitor in the decomposable rubber composition is appropriately adjusted according to the mass average molecular weight of the mixing rubber material and the content of the hydrolysis accelerator, so that the hydrolysis of the rubber molecules can be delayed and the sealing function as a sealing member can be maintained. That is, by increasing the content of the hydrolysis inhibitor in the decomposable rubber composition, the decomposition of the decomposable rubber composition can be further delayed.
[0041] [Other ingredients] The degradable rubber composition may contain, in addition to the above-mentioned components, for example, a reinforcing agent as appropriate.
[0042] The reinforcing agent is added to improve the strength of the rubber member when the decomposable rubber composition is used as a sealing member. As the reinforcing agent, for example, silicon dioxide, carbon black, etc. can be cited. It should be noted that when a mineral powder such as silicon dioxide is used as an acidic hydrolysis accelerator, the mineral powder can play two functions as an acidic hydrolysis accelerator and as a reinforcing agent. As the acidic hydrolysis accelerator, for example, mineral powders such as silicon dioxide, clay, talc, aluminum sulfate, barium sulfate, calcium sulfate, and aluminum oxide colloid can be cited.
[0043] [Method for producing degradable rubber composition] The method for producing the degradable rubber composition is not particularly limited, and a common production method can be used. That is, the degradable rubber composition can be produced, for example, by a production method including the following steps: a kneading step in which raw materials containing at least a degradable rubber component and an acidic hydrolysis accelerator are kneaded; and a vulcanization step in which the kneaded raw materials are subjected to a crosslinking reaction.
[0044] The kneading method for kneading the raw materials in the kneading step is not particularly limited, and the kneading may be carried out by an open roll mill, a pressure kneader, a Banbury mixer or the like.
[0045] After the degradable rubber composition is obtained, there is no particular limitation on the method for producing a rubber member. For example, the degradable rubber member can be produced by placing the degradable rubber composition in a predetermined mold and vulcanizing it under predetermined vulcanization conditions.
[0046] Regarding the vulcanization conditions for vulcanizing the degradable rubber composition, for example, the temperature can be set to a range of 120°C to 200°C and a time of about 5 to 60 minutes. When the temperature is lower than 120°C, the crosslinking agent is not decomposed and the crosslinking reaction of the rubber does not occur. In addition, if the temperature exceeds 200°C, the compound (polymer) is degraded. On the other hand, in the range of 120°C to 200°C, crosslinking of the rubber occurs and degradation of the polymer does not occur. The range of time is also the same. As a vulcanizing agent, sulfur or an organic peroxide can be used. As an organic peroxide, for example, peroxy ketal, dialkyl peroxide, diacyl peroxide, peroxy ester, etc. can be cited.
[0047] [Hydraulic fracturing] Next, hydraulic fracturing is described. As an example of using the sealing member of this embodiment, hydraulic fracturing is described. Figure 6 The method is the same as described in Figure 6 However, as described later, the sealing member of the present embodiment is formed using the degradable rubber composition according to the present embodiment, and the material of the rubber member is different from that of the conventional sealing member 100 .
[0048] [Sealing member 1] Figure 1 Schematic diagram showing a sealing member formed using the degradable rubber composition according to Embodiment 1. Figure 1 As shown, the sealing component 1 includes: a main body 2 having a roughly cylindrical shape extending along the length direction L; a pair of sleeves 4, which are arranged on both end sides of the length direction L of the main body 2 in a manner that allows sliding along the length direction L; and a rubber component 3, which is arranged between the pair of sleeves 4. Figure 1 (a) is a schematic diagram showing a state in which the pair of sleeves 4 are located at predetermined positions and the rubber member 3 is not compressed. Figure 1 (b) is a schematic diagram showing a state in which the pair of sleeves 4 are located at a position moved toward the center side (rubber member 3 side) in the length direction L, and the rubber member 3 is compressed. Here, the "length direction L" is the direction in which the substantially cylindrical tube of the sealing member 1 extends, and refers to the direction in which the central axis extends, and is the direction in which the sealing member 1 moves in the excavated hole 13. In addition, the "two end sides in the length direction L" refer to the front end side and the rear end side when the sealing member 1 moves in the excavated hole 13.
[0049] [Rubber member 3] The rubber member 3 is a member formed of the degradable rubber composition according to the first embodiment. As described above, the rubber member 3 is disposed between the pair of sleeves 4 and is a tubular member covering the periphery of the main body 2. Figure 1 As shown in (b), the rubber member 3 is deformed by being compressed by the pair of sleeves 4 and expands in a direction substantially perpendicular to the longitudinal direction. As a result, the diameter (diameter substantially perpendicular to the longitudinal direction) of the sealing member 1 increases in the portion of the rubber member 3. In this way, the rubber member 3 is tightly attached to the wall surface of the excavated hole 13 by the expansion of the rubber member 3, and the excavated hole 13 can be sealed.
[0050] After the sealing member 1 has finished sealing the excavation hole 13, the rubber member naturally disintegrates and is removed. The rubber member 3 is formed by the decomposable rubber composition involved in this embodiment. The decomposable rubber composition of the rubber member 3 constituting the sealing member 1 has a sealing function and has a function of flake-forming even if no stress is applied from the outside after a predetermined time. The parts other than the rubber member 3 constituting the sealing member 1, namely the main body 2 and a pair of sleeves 4, can be formed by the decomposable rubber composition or by other decomposable raw materials. As such decomposable raw materials, for example, polyglycolic acid (PGA), polylactic acid (PLA) and the like can be cited. The parts other than the rubber member 3 constituting the sealing member 1 are preferably decomposed in a time substantially equal to the decomposition time of the decomposable rubber composition. It should be noted that the decomposable rubber composition of this embodiment is not limited to the above-mentioned hydraulic fracturing method, and can also be used in other methods requiring sealing performance, decomposition performance and disintegration performance.
[0051] Example Hereinafter, specific examples of the present invention will be described by way of examples. It should be noted that the present invention is not limited to the following examples.
[0052] [Example 1] As raw materials, 100 parts by mass of polyester-based kneaded polyurethane rubber as a degradable rubber component and 40 parts by mass of silica as an acidic hydrolysis accelerator and reinforcing agent were used. The degradable rubber component was kneaded using an open roll mill, and the hydrolysis accelerator was added as an additive, and further kneaded to obtain the degradable rubber composition of Example 1.
[0053] The obtained decomposable rubber composition is put into a mold and heated under pressure at 120 to 200° C. for 5 to 60 minutes to vulcanize. An organic peroxide is used as a vulcanizing agent. A cubic rubber sample with one side of 20 mm is prepared. A plurality of rubber samples are prepared corresponding to each immersion time described later.
[0054] [Decomposability evaluation test] Each rubber sample and ion exchange water having a volume 10 times the volume of the rubber sample were added to a 200 mL glass bottle, and each rubber sample and ion exchange water were placed in an oven set at 93° C. for a predetermined immersion time. The immersion time was 1 day, 3 days, 5 days, 7 days, 9 days, and 11 days.
[0055] Each rubber sample after being placed in the oven for each immersion time was taken out from the ion exchange water and placed at room temperature to dry. Then, for each rubber sample, the surface hardness (HsA) was measured using a hardness meter type A (JIS K 6253, Kobunsu Keiki Co., Ltd.). The surface hardness was measured as the value after applying a load of 1 kg for 3 seconds. It should be noted that as the surface hardness on day 0, the value measured before the rubber sample was immersed in the ion exchange water was used.
[0056] The results of surface hardness measurement are shown in Figure 2 . Figure 2 : is a graph showing the results of measuring the surface hardness of the rubber samples of Example 1 and Comparative Examples 1 and 2. Figure 2 In the graph of , the vertical axis represents the surface hardness (HsA) and the horizontal axis represents the immersion time (days). Figure 2 It is indicated by "●" (solid circle) in the figure. It is known that the surface hardness (HsA) of the rubber sample of Example 1 becomes 0 (zero) 7 days after the start of immersion.
[0057] Figure 3 Schematic diagram showing the state of the rubber sample of Example 1 before and after natural disintegration. Figure 3 (a) is a schematic diagram showing the state immediately after the rubber sample 30 is made. At this time, the rubber sample 30 maintains a cubic shape with one side of 20 mm, and the degradable rubber component is not decomposed. It should be noted that the state before immersion is not limited to Example 1, and is the same in other Examples and Comparative Examples. Figure 3 (b) means that a glass bottle 34 containing ion exchange water 36 is placed. Figure 3 (a) is a schematic diagram showing a state in which the rubber sample 30 has naturally disintegrated 7 days after the start of immersion. Figure 3 (b) shows a state where small pieces 32 of the naturally disintegrated rubber sample 30 are precipitated in ion exchange water 36 at the bottom of a glass bottle 34 . Figure 3 The small pieces 32 of the naturally disintegrated rubber sample 30 shown in (b) are, for example, fragmented to less than 1 mm and are in a powdery state when taken out of the glass bottle 34. This shows that the rubber sample 30 of Example 1 disintegrated naturally 7 days after the start of immersion.
[0058] [Comparative Example 1] The rubber samples were prepared in the same manner as in Example 1, except that the content of the hydrolysis accelerator was 20 parts by mass relative to 100 parts by mass of the degradable rubber component, and the surface hardness (HsA) was measured. Figure 2It is indicated by "□" (hollow quadrilateral) in the figure. It is found that the surface hardness (HsA) of the rubber sample of Comparative Example 1 becomes 0 (zero) 7 days after the start of immersion.
[0059] Figure 4 It is a schematic diagram showing the state of the rubber samples of Comparative Examples 1 and 2 after decomposition. Figure 4 (a) is a schematic diagram showing the rubber sample 300 of Comparative Example 1 placed in a glass bottle 34 filled with ion exchange water 36, and the rubber sample 300 of Comparative Example 1 after decomposition, that is, 7 days after the start of immersion. Figure 4 (a) shows that the rubber sample 300 is decomposed but does not disintegrate naturally, and maintains a cubic shape close to the state of the rubber sample 300 of Comparative Example 1 immediately after the preparation. In this regard, it is different from the state of the rubber sample 300 of Example 1 after it disintegrates naturally. Figure 3 The surface hardness (HsA) of the rubber sample 300 of Comparative Example 1 became 0 (zero) (decomposed) 7 days after the start of immersion, but it had high viscosity like clay and maintained a cubic shape. In other words, the rubber sample 300 of Comparative Example 1 did not disintegrate naturally.
[0060] [Comparative Example 2] The rubber samples were prepared in the same manner as in Example 1, except that the content of the hydrolysis accelerator was 30 parts by mass relative to 100 parts by mass of the degradable rubber component, and the surface hardness (HsA) was measured. Figure 2 It is indicated by "△" (hollow triangle) in the figure. It is known that the surface hardness (HsA) of the rubber sample of Comparative Example 2 becomes 0 (zero) 7 days after the start of immersion.
[0061] Figure 4 (b) is a schematic diagram showing the state of the rubber sample 310 of Comparative Example 2 after the rubber sample 310 of Comparative Example 2 is put into the glass bottle 34 filled with ion exchange water 36, and after the rubber sample 310 of Comparative Example 2 is decomposed, that is, 7 days after the immersion starts. Figure 4 (b) shows a state where the rubber sample 310 of Comparative Example 2 is poked with a stick 7 days after the start of immersion, but does not disintegrate naturally. In other words, the rubber sample 310 of Comparative Example 2 is in a state where the shape is destroyed by applying an external force, although the rubber sample 310 is decomposed 7 days after the start of immersion. The surface hardness (HsA) of the rubber sample 310 of Comparative Example 2 becomes 0 (zero) (decomposed) but has a high viscosity like clay. In other words, the rubber sample 310 of Comparative Example 2 does not disintegrate naturally. The shape of the rubber sample 310 of Comparative Example 2 is destroyed by applying stress from the outside.
[0062] [Example 2] Rubber samples were prepared in the same manner as in Example 1, and the surface hardness (HsA) was measured. The measurement results are shown in Figure 5 . Figure 5 : is a graph showing the results of measuring the surface hardness of the rubber samples of Examples 2 to 4. The measurement results of Example 2 are shown in FIG. Figure 5 Indicated by "●" (solid circle). It can be seen that the rubber sample of Example 2, like Example 1, has a surface hardness (HsA) of 0 (zero) 7 days after the start of immersion. The rubber sample of Example 2, like Example 1, disintegrated naturally 7 days after the start of immersion.
[0063] [Example 3] A rubber sample was prepared in the same manner as in Example 1, except that 3 parts by mass of a high molecular weight carbodiimide compound was added as a hydrolysis inhibitor to 100 parts by mass of the degradable rubber component, and the surface hardness (HsA) was measured. Figure 5 Indicated by "▲" (black triangle). It can be seen that the surface hardness (HsA) of the rubber sample of Example 3 becomes 0 (zero) 9 days after the start of immersion. The rubber sample of Example 3 disintegrated naturally 9 days after the start of immersion, just like Example 1. It can be seen that the hydrolysis of the degradable rubber component is suppressed by adding the hydrolysis inhibitor. Figure 5 As can be seen from the graph, the surface hardness (HsA) of the rubber sample of Example 3 was maintained at about 80 from the start of immersion to about the fifth day, and then the surface hardness decreased to 0 HsA on the ninth day. It is inferred from this that the rubber sample of Example 3 was inhibited from decreasing in surface hardness by the action of the hydrolysis inhibitor from the start of immersion to about the fifth day, and then the surface hardness decreased by the hydrolysis of the degradable rubber component.
[0064] [Example 4] A rubber sample was prepared in the same manner as in Example 1, except that 4.5 parts by mass of a high molecular weight carbodiimide compound was added as a hydrolysis inhibitor to 100 parts by mass of the degradable rubber component, and the surface hardness (HsA) was measured. Figure 5 Indicated by "■" (black rectangle). It can be seen that the surface hardness (HsA) of the rubber sample of Example 4 becomes 0 (zero) 11 days after the start of immersion. The rubber sample of Example 4 disintegrated naturally 11 days after the start of immersion, just like Example 1. It can be seen that the hydrolysis of the degradable rubber component is suppressed by adding the hydrolysis inhibitor. Figure 5As can be seen from the graph, the surface hardness (HsA) of the rubber sample of Example 4 was maintained at about 80 from the start of immersion to about the fifth day, and then the surface hardness decreased to 0 HsA on the eleventh day. It is speculated that the rubber sample of Example 4 suppressed the decrease in surface hardness from the start of immersion to about the fifth day by the action of the hydrolysis inhibitor, and then the surface hardness was reduced by hydrolysis of the degradable rubber component. In addition, it is speculated that the amount of hydrolysis inhibitor added to the rubber sample of Example 4 is larger than that of Example 3, so even after the fifth day from the start of immersion, the hydrolysis is suppressed by the action of the hydrolysis inhibitor, the decrease in surface hardness (the slope of the curve) becomes slower, and the time from the start of immersion to natural disintegration becomes longer.
[0065] The above results show that the degradable rubber composition according to the present invention can form a rubber member that naturally disintegrates after a predetermined time has passed since it was immersed in 93° C. water by containing 40 parts by mass or more of a hydrolysis accelerator based on 100 parts by mass of the degradable rubber composition.
[0066] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications and changes can be made within the scope of the gist of the present invention. For example, the present invention includes the following gist.
[0067] (Subject 1) The invention relates to a method of producing a rubber composition comprising a kneadable rubber component and an acidic hydrolysis accelerator, wherein the decomposable rubber component comprises a kneadable rubber material composed of rubber molecules capable of hydrolyzing, the acidic hydrolysis accelerator is a powder which exhibits acidity upon contact with water and accelerates the hydrolysis of the rubber molecules upon contact with water, and the amount of the acidic hydrolysis accelerator contained is 40 parts by mass or more per 100 parts by mass of the decomposable rubber component.
[0068] According to the first aspect, a degradable rubber composition can be provided which has sealing performance as a rubber member of a sealing member and can be easily removed by breaking into small pieces even without external stress after being continuously exposed to a fluid such as water for a predetermined period of time.
[0069] (Subject 2) The present invention may contain an alkaline hydrolysis accelerator, which is a powder that exhibits alkalinity upon contact with water and promotes hydrolysis of the rubber molecules upon contact with water, wherein the alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more based on 100 parts by mass of the degradable rubber component.
[0070] According to the second aspect, the hydrolysis of the degradable rubber component can be further promoted.
[0071] (Subject 3) The mass average molecular weight of the rubber molecules may be 10,000 or more.
[0072] According to the third aspect, it is possible to select a kneading type rubber material within a range of sizes more suitable for natural disintegration.
[0073] (Subject 4) The present invention provides a rubber member comprising the degradable rubber composition according to any one of Subjects 1 to 3.
[0074] (Subject 5) The subject matter is a sealing member including the rubber member according to Subject 4 as at least a part thereof.
[0075] According to the fourth and fifth aspects, a rubber member and a sealing member can be provided which have the sealing performance of a rubber member as a sealing member and can be easily removed by being cut into small pieces even without external stress after being continuously exposed to a fluid such as water for a predetermined time.
[0076] (Subject 6) The invention relates to a method of kneading a raw material, wherein the raw material contains a degradable rubber component and an acidic hydrolysis accelerator, wherein the degradable rubber component comprises a kneadable rubber material composed of rubber molecules capable of hydrolyzing, and the acidic hydrolysis accelerator is a powder which exhibits acidity by contact with water and promotes hydrolysis of the rubber molecules by contact with water, wherein the acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more per 100 parts by mass of the degradable rubber component.
[0077] According to the sixth aspect, a method for producing a degradable rubber composition can be provided, wherein the degradable rubber composition has sealing performance as a rubber member as a sealing member and can be easily removed by being broken into small pieces even without external stress after being continuously exposed to a fluid such as water for a predetermined period of time.
[0078] Description of Reference Numerals 1,100 Sealing components 2 Main body 3 Rubber components 4 Sleeve 5 Catheter 10 pits 11 Surface 13 Digging Holes 15 Crack 30, 300, 310 rubber samples 32 Small pieces of rubber sample 34 Glass Bottle 36 Ion exchange water 50 Basement 51 Mining Layer L Length direction.
Claims
1. A degradable rubber composition, characterized in that: Contains degradable rubber components and acid hydrolysis accelerators. The degradable rubber component includes a kneadable rubber material composed of rubber molecules that can be hydrolyzed. The acidic hydrolysis accelerator is a powder that becomes acidic when in contact with water and accelerates the hydrolysis of the rubber molecules when in contact with water. The acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more based on 100 parts by mass of the degradable rubber component.
2. The degradable rubber composition according to claim 1, wherein The degradable rubber composition contains an alkaline hydrolysis accelerator, which is a powder that exhibits alkalinity upon contact with water and accelerates hydrolysis of the rubber molecules upon contact with water. The alkaline hydrolysis accelerator is contained in an amount of 1 part by mass or more based on 100 parts by mass of the degradable rubber component.
3. The degradable rubber composition according to claim 1 or 2, wherein: The mass average molecular weight of the rubber molecules is greater than 10,000.
4. A rubber component, characterized in that: The degradable rubber composition according to claim 1.
5. A sealing member, characterized in that: The rubber member according to claim 4 is provided as at least a part thereof.
6. A method for producing a degradable rubber composition, characterized in that: The method comprises a kneading step of kneading raw materials, wherein the raw materials contain a degradable rubber component and an acidic hydrolysis accelerator, wherein the degradable rubber component comprises a kneadable rubber material composed of rubber molecules capable of hydrolysis, and the acidic hydrolysis accelerator is a powder that exhibits acidity when in contact with water and promotes hydrolysis of the rubber molecules when in contact with water. The acidic hydrolysis accelerator is contained in an amount of 40 parts by mass or more based on 100 parts by mass of the degradable rubber component.
Citation Information
Patent Citations
Method for collection of gaseous hydrocarbon and / or liquid hydrocarbon from underground
JP2015059376A